Cancer Incidence and Mortality Among Fighter Aviators in the United States Air Force. Issue 1 (January 2022) - Webber, Bryant J.; Tacke, Crystal D.; Wolff, Gregory G.; Rutherford, Ashley E.; Erwin, William J.; Escobar, James D.; Simon, Alisa A.; Reed, Brian H.; Whitaker, Justin G.; Gambino-Shirley, Kelly J.; Stuever, David M.
Abstract : Objective: This study sought to clarify cancer risk in fighter aviators. Methods: US Air Force officers who served between 1970 and 2004 were followed through 2018 for incidence and mortality of 10 cancers: colon and rectum; pancreas; melanoma skin; prostate; testis; urinary bladder; kidney and renal pelvis; brain and other nervous system; thyroid; and non-Hodgkin lymphoma. Fighter aviators were compared with other officers and the general US population. Results: Compared with other officers, male fighter aviators had greater adjusted odds of developing testis, melanoma skin, and prostate cancers; mortality odds were similar for all cancers. When compared with the US population, male fighter aviators were more likely to develop and die from melanoma skin cancer, prostate cancer, and non-Hodgkin lymphoma. Conclusions: Military fighter aviation may be associated with slightly increased risk of certain cancers. Abstract : Supplemental Digital Content is available in the text